EFFECTS OF ZEOLITE AND BLOOD FLOUR RATE AS THE SOURCE OF PROTEIN ON RANSOM ON PIG CARCASS QUALITY - Pollung H. Siagian; Muladno Muladno; Alfonsus Agan Gurmilang (Jurnal Zeolit Indonesia, 2003)
The objectives of this research is to know the effects of zeolite and blood flour rate effects as the source of protein on ransom on pig carcass quality. Pig carcass quality is influenced by several factors before and after slaughtering. One of the factors that influences pig carcass before slaughtering is feeding. The right feeding can fulfill the pig needs and increases the pig carcass quality. The average weight of 27 pigs used on this research is 25,59 ± 2,67 kg and the research design is 3´3 complete randomize design which the first factor is zeolite rate (0, 3, and 6%) and second rate is blood flour rate (0, 5, and 10%), so we have nine treatments ransom (R1 to R9) with three repetition on each treatment. The result showed that zeolite rate on ransom did not affect any parameter (P>0,05) and neither the blood flour, except for the loin eye area larger than 10% and without blood flour on ransom with the scores 31,16 ± 4,25; 27,74 ± 3,32, and 29,18 ± 4,85 cm2. The effect of interaction between zeolite rate and blood flour on ransom is very real (P0,05) on carcass percentage and the thickness of pig carcass back fat. The highest and the lowest slaughter weight and carcass weight is the pig whose have R5 and R4. The highest average of back fat thickness and loin eye area is the pig whose have R8 and R4 is the lowest. The pig whose have R7 and R4 each have the longest and shortest carcass while the highest carcass percentage is the pig whose have R4 and the lowest is R6.